PERAN PENGADILAN AGAMA DALAM PENANGANAN DAN PENANGGULANGAN PERCERAIAN - Samun Ismaya (Kajian Hukum, 2017)
This research is based on the fact that the number of divorce rate that occurred in Gunung Kidul regency recently, even on average there are about 100 divorce decisions every six months and this has not been the case of divorce into the Religious Courts. With this high divorce rate becoming a further interest to study it in a study of the role of government in this case the Religious Courts in the effort to overcome and handling Divorce in Gunung Kidul Regency in addition to looking for the reasons why the divorce rate is so high.In the concept of the State welfare law, the government has an obligation to play an active role in creating prosperity for the community in the form of creating an atmosphere of tranquility, happiness and order in various aspects of community life, especially in the family field. The function and role of government which are then deregulated in various organs and government institutions are so dominant in creating the ideals of the welfare state law.This research was conducted by using normative legal research methods supported by secondary data in the form of legal materials and data relating to the role of government in this case the Religious Court in the control and handling of divorce that occurred in Gunung Kidul Regency.In literature research that will produce secondary data is done by studying the documents relating to the research topic which is then analyzed by using qualitative analysis based on the norms or theories applicable which then described in the form of identification, analysis and then compiled back in order to draw conclusions. The results of this study are expected to be useful for the development of science, especially the science of law and more specifically the law of State administration and constitutional law. Besides, this research is also expected to provide inputs in an effort to maximize the role of government in creating community welfare through efforts to overcome and decrease divorce rate that occurred in Gunung Kidul Regency. Keywords: Role of PA, handling, handling, divorce